Cycle training modulates satellite cell and transcriptional responses to a bout of resistance exercise. Issue 18 (20th September 2016) - Murach, Kevin A.; Walton, R. Grace; Fry, Christopher S.; Michaelis, Sami L.; Groshong, Jason S.; Finlin, Brian S.; Kern, Philip A.; Peterson, Charlotte A.
Abstract: This investigation evaluated whether moderate‐intensity cycle ergometer training affects satellite cell and molecular responses to acute maximal concentric/eccentric resistance exercise in middle‐aged women. Baseline and 72 h postresistance exercise vastus lateralis biopsies were obtained from seven healthy middle‐aged women (56 ± 5 years, BMI 26 ± 1, VO2max 27 ± 4) before and after 12 weeks of cycle training. Myosin heavy chain (MyHC) I‐ and II‐associated satellite cell density and cross‐sectional area was determined via immunohistochemistry. Expression of 93 genes representative of the muscle‐remodeling environment was also measured via NanoString. Overall fiber size increased ~20% with cycle training ( P  = 0.052). MyHC I satellite cell density increased 29% in response to acute resistance exercise before endurance training and 50% with endurance training ( P  < 0.05). Following endurance training, MyHC I satellite cell density decreased by 13% in response to acute resistance exercise (acute resistance × training interaction, P  < 0.05). Genes with an interaction effect tracked with satellite cell behavior, increasing in the untrained state and decreasing in the endurance trained state in response to resistance exercise. Similar satellite cell and gene expression response patterns indicate coordinated regulation of the muscle environment to promote adaptation. Moderate‐intensity endurance cycle training modulates the response to acute resistance exercise, potentially conditioning the muscle for more intense concentric/eccentric activity. These results suggest that cycle training is an effective endurance exercise modality for promoting growth in middle‐aged women, who are susceptible to muscle mass loss with progressing age. Abstract : This investigation evaluated whether moderate‐intensity cycle ergometer training affects satellite cell and molecular responses to acute maximal concentric/eccentric resistance exercise in middle‐aged women. Moderate‐intensity endurance cycle training modulates the response to acute resistance exercise, potentially conditioning the muscle for more intense concentric/eccentric activity. Furthermore, cycle training is an effective endurance exercise modality for promoting growth, specifically in middle‐aged women who are susceptible to muscle mass loss with progressing age.